2020
DOI: 10.7759/cureus.9708
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Psoriasis and Depression: A Traditional Review

Abstract: Psoriasis is a chronic inflammatory disease of the skin with multiple comorbidities, depression being one of them. Psoriasis affects the personal, social, and sexual lives of the patients resulting in psychological strain. Psoriasis and depression amplify each other. Supporting evidence has proven multiple common mechanisms between the two diseases: inflammatory overlap, genetic evidence, low vitamin D3, and melatonin levels are common in both psoriasis and depression. Fear of social rejection and self-stigmat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 46 publications
1
32
1
Order By: Relevance
“…A recent meta-analysis found that patients with psoriasis appear to have a slightly increased risk of cancer, particularly keratinocyte cancer and lymphomas, although data for National and International Registries on treatment with biologic agents did not show an increased risk of cancer, and data on cancer in patients with psoriatic arthritis remain inconclusive [ 104 ]. The prevalence of having depression or anxiety is higher in psoriasis patients than in controls, and TNF-α could be a pathophysiologic link between the two conditions [ 105 , 106 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent meta-analysis found that patients with psoriasis appear to have a slightly increased risk of cancer, particularly keratinocyte cancer and lymphomas, although data for National and International Registries on treatment with biologic agents did not show an increased risk of cancer, and data on cancer in patients with psoriatic arthritis remain inconclusive [ 104 ]. The prevalence of having depression or anxiety is higher in psoriasis patients than in controls, and TNF-α could be a pathophysiologic link between the two conditions [ 105 , 106 ].…”
Section: Resultsmentioning
confidence: 99%
“…Patients with psoriasis who show high levels of cytokines, Th17 cells and IL-17A, are more subjected to develop depression and anxiety disorders [ 144 ]. These data suggest a strong correlation between depression and the immune system; therefore, a relationship between depression and psoriasis may be hypothesized [ 157 ]: depression improvement might be observed following treatment of psoriasis, and conversely, depression treatment might improve psoriasis symptoms [ 157 ].…”
Section: Psoriasis-related Psychological Alterationsmentioning
confidence: 99%
“…The higher prevalence of obesity in psoriasis patients may be related not only to the overproduction of pro-inflammatory factors, but also to the fact that psoriasis is often accompanied by stigma and prolonged stress, which often lead to reduced levels of physical activity as well as adverse changes in eating habits and broader lifestyle. These, in turn, may contribute to weight gain [ 26 , 27 ].…”
Section: Obesitymentioning
confidence: 99%
“…On the other hand, obesity may contribute to lower self-esteem, increased stress levels, and even the development or worsening of depression and anxiety disorders [ 26 ]. The relationship between psoriasis and obesity in a psychological context is shown in Figure 1 .…”
Section: Obesitymentioning
confidence: 99%
See 1 more Smart Citation